Best Answer

Simplifying

a = 3a + 12

Reorder the terms:

a = 12 + 3a

Solving

a = 12 + 3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3a' to each side of the equation.

a + -3a = 12 + 3a + -3a

Combine like terms: a + -3a = -2a

-2a = 12 + 3a + -3a

Combine like terms: 3a + -3a = 0

-2a = 12 + 0

-2a = 12

Divide each side by '-2'.

a = -6

Simplifying

a = -6

Study guides

☆☆

Q: How do you do this A x 3 a plus 12?

Write your answer...

Submit

Still have questions?

Related questions

-10x+3 = -x+12 -10x+x = 12-3 -9x = 9 x = -1

12!

-9

12

(x+3)(x+4) = x²+7x+12

x=-24

(x + 3)(x + 4) = x2 + 7x + 12

If you ignore the fact that the question contains the phrase "3 time's 3" which is without any meaning, the answer is 89333197.32.

x^2 +7x+12 = (x+3)(x+4) when factored

It is (x+3)(x+4) when factored

3 - 8 + 12 = x -5 + 12 = x 7 = x Answer : 7

(x+3)(x+4)=x2+7x+12

People also asked